Investitionsregulierung in Stromverteilnetzen - Wolfgang Elsenbast; Steffen Boche (Wirtschaftsdienst, 2013)
Die Energiewende in Deutschland verlangt von den Verteilnetzbetreibern erhebliche neue Investitionen. Dies ist bei der Regulierung der Netzentgelte hinreichend zu berücksichtigen. Hier sind neben den vorhandenen Anreizen zur Kosteneffizienz auch geeignete Anreize zur dynamischen Effizienz im Sinne der Steuerung von wirtschaftlichen Investitionen wichtig. Die Autoren diskutieren aktuelle Probleme der Investitionsregulierung und geben einen Überblick über mögliche Lösungen, die im Rahmen der Anreizregulierung der Netzentgelte von Verteilnetzbetreibern denkbar sind. – – Within the context of the German incentive regulation, several investment incentives for Distribution System Operators are discussed. The concrete design seems to be quite complex and certain trade-offs are inevitable. The time delay problem within the existing regulation can be better covered by an improved design of the network enlargement factor. Alternatively, simplified cost recognition schemes can be considered, but the extent to which they might improve cost efficiency must be analysed in more detail. Incentives can also be created by rate-of-return adders. A crucial problem with these adders is that their economic adequacy is often not clearly derived. Additional instruments, e.g. sliding scales for specific costs, which are not covered by the (potentially improved) instruments already available are also discussed.
Keywords: L51; L94; 330; Investition; Netzinfrastruktur; Anreizregulierung; Investitionspolitik; Elektrizitätswirtschaft; Deutschland